Integrated Study of Globally Expressed microRNAs in IL-1β-stimulated Human Osteoarthritis Chondrocytes and Osteoarthritis Relevant Genes: A Microarray and Bioinformatics Analysis. (2nd July 2016) - Rasheed, Zafar; Al-Shobaili, Hani A.; Rasheed, Naila; Al Salloom, Abdulaziz A. M.; Al-Shaya, Osama; Mahmood, Amer; Alajez, Nehad M.; Alghamdi, Ahmed S. S.; Mehana, El-Sayed E.
ABSTRACT: This study was undertaken to identify and characterize the globally expressed microRNAs (miRNAs) involved in interleukin-1β (IL-1β)-induced joint damage and to predict whether miRNAs can regulate the catabolic effects in osteoarthritis (OA) chondrocytes. Out of 1347 miRNAs analyzed by microarrays in IL-1β-stimulated OA chondrocytes, 35 miRNAs were down-regulated, 1 miRNA was up-regulated, and the expression of 1311 miRNAs remained unchanged. Bioinformatics analysis showed the key inflammatory mediators and key molecular pathways are targeted by differentially expressed miRNAs. Novel miRNAs identified could have important diagnostic and therapeutic potentials in the development of novel therapeutic strategies for pain managements in OA.